The Significance Of Ijtihad and Fatwa Methods in The Development Of Islamic Law In Indonesia - Agustono, Ihwan (Universitas Islam Negeri Sumatera Utara, 2024)
This article discusses the role of fatwas in the development of Islamic law, especially in Indonesia, which is institutionally represented by the Indonesian Ulema Council. The Qur'an and the Sunnah as the main sources of Islamic law are limited in terms of quantity, while the legal problems that arise in people's lives are increasingly complex and unlimited. To deal with various complex and novel problems, the legal requirements of which are sometimes not clearly stated in the Qur'an and the Sunnah, the application of ijtihad is absolutely necessary. One of the reasons for the formation of the Indonesian Ulema Council (MUI) was to face and respond to situations like this. As an Islamic institution that has the authority to issue fatwas, the MUI has an important position in the development of Islamic law in Indonesia. Therefore, the methods applied by the MUI in carrying out ijtihad and issuing fatwas related to various legal problems faced in society also have high urgency. This paper attempts to explore the ijtihad method used by the MUI in carrying out ijtihad and issuing fatwas. By using a qualitative approach, this research found that the MUI ijtihad method uses three approaches: the Nash Qath'i approach, the Qawli approach, and the Manhaji approach, which are based on the context.